NLRP3 inflammasome activation contributes to the cognitive decline after cardiac surgery - Ma, Gang; Sun, Ping; Chen, Yi; Jiang, Xin; Zhang, Caixia; Qu, Baofu; Meng, Xiangkun (Frontiers in Surgery, 2022)
Background: Perioperative neurocognitive disorders (PND) are a common complication of cardiac surgery in elderly patients. The etiopathogenesis of PND is not clear. Nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, a macromolecular protein complex, regulates inflammation by inducing the release of proinflammatory cytokines interleukin (IL)-1β and IL-18. Studies have demonstrated a close link between the NLRP3 inflammasome and central nervous system diseases. Nevertheless, the involvement of NLRP3 inflammasome in the causation of PND occurring after cardiac surgery is unclear. This study aimed to investigate the association of serum NLRP3 level with PND. Methods: We performed a retrospective study, enrolled 75 patients undergoing elective cardiac surgery and evaluated their cognitive functions one day before and 7 days after surgery. PND were determined according to the International Study of Postoperative Cognitive Dysfunction studies. Demographics and perioperative parameters were recorded. Perioperative serum NLRP3 protein, IL-1β, and IL-18 levels were monitored. Results: The PND incidence in our cohort was 33.33%. NLRP3 protein levels were significantly increased in all patients at each postoperative time-point after general anesthesia and cardiac surgery under cardiopulmonary bypass. Patients showing cognitive dysfunction had higher serum NLRP3 protein, caspase-1, IL-1β, and IL-18 levels immediately after the operation. Variables associated with the incidence of early PND were included in the regression models. After adjusting for confounding variables, high serum NLRP3 protein level at the end of the operation and old age were identified as independent predictors of PND. Conclusions: High serum NLRP3 protein level at the completion of cardiac surgery was associated with a higher risk of PND seven days after surgery. Trial registration: The study was registered at Clinicaltrials.gov (registration number: NCT04191642).